PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI KHUSUS, DAN LUAS WILAYAH TERHADAP BELANJA MODAL PADA PEMERINTAH KABUPATEN/KOTA DI PROVINSI ACEH - Maulana, Fajar; Fadhlia, Wida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This study aims to examine the effect of Local Revenue, Special Allocation Funds, and Area Size on Capital Expenditures. The data used in this study are secondary data obtained from the Aceh Financial Management Agency. The unit of analysis in this study is the 2014-2018 Regency/City Budget Realization Report. The sample in this study was Aceh Province consisting of 23 Regencies/Cities. The analysis technique used is multiple linear regression using SPSS 24. This study uses the independent variables Regional Original Revenue, Special Allocation Funds, and Area and the dependent variable Capital Expenditure. The results of this study indicate that in the simultaneous testing (F test), the variable Local Revenue, Special Allocation Funds, and Area Size have a significant effect on capital expenditure. . In the partial test, the variable of Original Regional Revenue, Special Allocation Funds, and area size affect capital expenditure.